Research into intelligent transport systems (ITS) technologies and efficiency - Jarašūnienė, Aldona (Transport, 2007)
Intelligent Transport Systems work with information and control technologies which provide the core of ITS functions. Some of these technologies, like loop detectors, are well known to transportation professionals. However, there are a number of less familiar technologies and system concepts that are the key to ITS functions. The technical core of ITS is information and control technologies, but human factors are also vitally important, and potentially very complex. This paper introduces the main ITS enabling technologies and explains why transport professionals should involve human factor experts at an early stage of design of ITS equipment and facilities.First Published Online: 27 Oct 2010